Shortcomings of and recommendations to improve double taxation relief mechanisms: a study of South African resident companies engaged in the exploration for and production of oil and gas outside of South Africa - Futter, Alison Jane (Department of Finance and Tax, 2022)
South African resident companies engaged in the exploration for and production of oil and gas outside of South Africa are subject to double taxation. This thesis evaluates whether South African resident companies engaged in the exploration for and production of oil and gas outside of South Africa receive full relief from double taxation in South Africa. The thesis provides a qualitative examination of the fundamental legal designs used for the allocation of the right to mine oil and gas and the fiscal regimes applied to the taxation of oil and gas mining at the source. The thesis explores the basis for taxation of foreign oil and gas income in South Africa and the remedies for double taxation in terms of the domestic tax legislation. Assuming that a tax treaty exists between South Africa and the host government, qualification for double taxation relief and classification of income in terms of a double taxation agreement (DTA) are evaluated. It is anticipated that a South African resident Oil and Gas company will choose the most favourable method and form of double tax relief when filing its corporate tax return in South Africa based on the commercial impact thereof. To aid in this decision, the thesis contrasts the quantum of the double tax relief under the domestic tax legislation with that available under the DTA. Using an adaptation of the IMF's FARI methodology, a quantitative analysis of the economic impact for a South African resident Oil and Gas company mining in Egypt, Equatorial Guinea, Ghana and, Nigeria is examined. The thesis concludes that there are circumstances where South African resident Oil and Gas companies are unable to achieve full double tax relief under the domestic tax legislation and make recommendations (where applicable) for amendments to the domestic tax legislation to achieve a form of full double tax relief as close as possible to the single tax principle.